2023
DOI: 10.1371/journal.pone.0285439
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring Chinese and Ethiopian higher VET adolescent learning motivation through the lens of self‑determination theory

Abstract: Ethiopia and China share a common educational agenda in cultivating and obtaining competent vocational graduates who fulfill the need of the modern, technologically advanced industrial workplace. Unlike most evidence, the present study adopted Self-determination Theory to understand Ethiopian and Chinese higher Vocational education and Training (VET) college students’ learning motivation. Hence, this study recruited and interviewed 10 volunteers senior higher VET students from each setting to unfold their sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…23 Motivasi belajar merujuk pada dorongan internal yakni motivasi belajar dapat muncul dari dalam diri individu sebagai hasil dari keinginan untuk tumbuh, berprestasi, dan memenuhi kebutuhan pribadi. 24 Dorongan ini dapat berasal dari keinginan intrinsik, seperti rasa ingin tahu, kepuasan pribadi, pencapaian, dan minat terhadap suatu subjek atau topik. 25 Selain itu motivasi belajar muncul dari faktor eksternal, yakni yang mempengaruhi perilaku seseorang dalam memulai, mempertahankan, dan mengarahkan upaya belajar, contohnya eksternal termasuk pujian, penghargaan, pengakuan, harapan orang tua atau guru, dan faktor-faktor lingkungan yang mendorong individu untuk belajar dan mencapai tujuan akademik.…”
Section: Muhammadiyah Galurunclassified
“…23 Motivasi belajar merujuk pada dorongan internal yakni motivasi belajar dapat muncul dari dalam diri individu sebagai hasil dari keinginan untuk tumbuh, berprestasi, dan memenuhi kebutuhan pribadi. 24 Dorongan ini dapat berasal dari keinginan intrinsik, seperti rasa ingin tahu, kepuasan pribadi, pencapaian, dan minat terhadap suatu subjek atau topik. 25 Selain itu motivasi belajar muncul dari faktor eksternal, yakni yang mempengaruhi perilaku seseorang dalam memulai, mempertahankan, dan mengarahkan upaya belajar, contohnya eksternal termasuk pujian, penghargaan, pengakuan, harapan orang tua atau guru, dan faktor-faktor lingkungan yang mendorong individu untuk belajar dan mencapai tujuan akademik.…”
Section: Muhammadiyah Galurunclassified
“…After publication of this article [ 1 ], concerns were raised about the article’s authorship, including the corresponding author designation. At this time, the PLOS ONE Editors have been unable to verify the information provided by the authors and consider these concerns unresolved.…”
mentioning
confidence: 99%
“…
The PLOS ONE EditorsAfter publication of this article [1], concerns were raised about the article's authorship, including the corresponding author designation. At this time, the PLOS ONE Editors have been unable to verify the information provided by the authors and consider these concerns unresolved.During post-publication editorial review of this article, additional concerns were raised about the ethics approvals reported in the study.
…”
mentioning
confidence: 99%
See 1 more Smart Citation